Adoption of retrofit measures among home-owners in EU countries: The effects of access to capital and debt aversion - Joachim Schleich; Corinne Faure; Thomas Meissner (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2019)
Energy efficiency policies often involve low-interest loans for retrofit measures in private buildings; the main target of these loans are meant to be households with otherwise poor access to capital. However, such programs can only be successful if the targeted households also take up these loans. This paper stud-ies the relation between access to capital and debt aversion and the adoption of retrofit measures in European Union countries, employing a demographically representative household survey including about 6,600 homeowners in France, Germany, Italy, Poland, Romania, Spain, Sweden, and the United Kingdom. The findings suggest that debt aversion negatively affects the adoption of retro-fit measures by homeowners. In particular, debt-averse homeowners with poor access to capital are less likely to have adopted retrofit measures than non-debt-averse homeowners with poor access to capital. The findings further pro-vide evidence that low-interest loan programs should be targeted at younger homeowners with lower income and less formal education.
urn:nbn:de:0011-n-5618477
Keywords: 330; energy efficiency; debt aversion; soft loans; energy policy; econo-metrics